Synergistic interaction of lithium ions and α1-adrenoceptor agonists in vascular and non-vascular porcine smooth muscle - Yahya, Saif (2019)
Phenylephrine, L-erythromethoxamine and metaraminol are selective α1-adrenoceptor agonists having phenethylamine chemical structure and used to treat a variety of clinical conditions, including sepsis, anaesthesia associated hypotension, nasal congestion, haemorrhoids, and the evaluation of eye function. Their action involves activation of α1-adrenoceptor on the smooth muscle of major organs to induce a contraction and the resultant therapeutic benefit is dependent on the maintenance of stable response. The signalling mechanism most closely linked to α1-adrenoceptors in smooth muscle is stimulation of phosphatidylinositol metabolism, which induces subsequent elevation of intracellular calcium ions. Lithium ions are also used clinically in the treatment of bipolar disorders and are known to prevent degradation of a key mediator of phosphoinositide metabolism and there are a few reports suggest that this cation can enhance or maintain contractions mediated by α1-adrenoceptors. In the present study, I have investigated the interaction between lithium ions and constrictor responses to a variety of agonists, including selective α1-adrenoceptor agonists, with a particular focus on both the potency of the constrictor agent and the time course of responses. I have also used pharmacological approaches to better understand the basis of a novel interaction between lithium ions and selective α1-adrenoceptor agonists.